Biochemical evaluation on rural workers exposed to pesticides - Simoniello, María Fernanda; Kleinsorge, Elisa C; Carballo, Marta A (Medicina (Buenos Aires), 2010)
Pesticides are used in agriculture to protect crops but may represent a potential risk to farmers and the environment. The aim of this work was to evaluate horticultural workers exposed to pesticide, categorized by: direct exposure (n = 45), indirect exposure (n = 50) and controls (n = 50) using exposure and effect biomarkers: cholinesterase (ChE), acetylcholinesterase (AChE), catalase (CAT), lipid peroxidation (TBARS), Damage Index Comet Assay (IDEC) and Damage Index Repair Assay (IDER). Our results show: a) an AChE inhibition in directly and indirectly exposed population (p < 0.001), b) significant increase in the levels of TBARS in direct exposure (p < 0.001), c) the CAT reduction was significant (p < 0.01), d) a significant increase in IDEC and IDER in both exposed groups (p < 0.001). Our results evidence variations in oxidative balance and DNA damage in exposed workers. These findings represent a contribution to the sub-clinical evaluation of subjects exposed to agrochemicals in our country.